Demographic and Psychological Determinants of COVID-19 Vaccine Hesitancy: A Comparative Analysis of Fully Vaccinated and Unvaccinated Populations in Babol, Iran - Mohammad Khadamlou; Mahmoud Mousazadeh; Afsoun Mahouri (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Vaccine hesitancy during epidemics poses significant challenges to healthcare systems. Despite the availability of vaccines, some individuals refuse vaccination, delaying disease control and exacerbating the health, economic, and psychological consequences. This study aimed to investigate the factors associated with COVID-19 vaccine hesitancy in Babol, Iran. Materials and methods: In a cross-sectional analytical study, 570 individuals aged 18 years and older and under urban family physician coverage were evaluated during a two-month period (August–September 2022). Participants were divided into two groups: 285 vaccine-hesitant individuals (mean age: 37 years) and 285 fully vaccinated individuals (three doses, mean age: 42 years). Data were collected using a standardized questionnaire assessing demographic, social, psychological, and behavioral factors. Statistical analyses, including Chi-square, Fisher’s exact test, Shapiro-Wilk test, and Mann-Whitney U test, were performed using SPSS version 26. Logistic regression was applied to adjust for potential confounding variables. Results: Univariate analysis revealed significant associations between vaccine hesitancy and age (P=0.000), marital status (P=0.017), education level (P=0.000), and income (P=0.003). Hesitancy was also linked to a history of physical (P=0.007) or mental illness (P=0.004), and prior COVID-19 infection (P=0.002). No significant associations were observed with perceived health status (P=0.280), family history of COVID-19 (P=0.232), or health anxiety (P=0.500). Multivariate logistic regression analysis, after adjusting for confounding variables, showed significant associations between vaccine hesitancy and perceived risk (Adjusted OR =1.78; 95% CI: 1.68–1.90), trust (Adjusted OR = 1.86; 95% CI: 1.77–1.95), social responsibility (Adjusted OR = 1.87; 95% CI: 1.78–1.97), barriers (Adjusted OR = 2.10; 95% CI: 2.01–2.20), and perceived cost-benefit (Adjusted OR = 2.40; 95% CI: 2.23–2.59). Conclusion: COVID-19 vaccine hesitancy was more prevalent among younger, single individuals with lower levels of education and income. It was associated with reduced risk perception, low trust in healthcare systems, negative attitudes toward vaccination, and environmental barriers, but not associated with perceived health, family history of COVID-19, or health anxiety. Targeted interventions addressing demographic and attitudinal factors are essential for improving vaccine uptake.